Critical Review On Muslim Code Pd1083: A Basis For A New Enactment Of Expanded Islamic Code Of The Muslim Personal Law In The Barmm - Abdulcader M. Ayo; Anwar M. Radiamoda (AIUA Journal of Islamic Education, 2019)
This study aimed to find out the views of the Meranaw, Tausog and Maguindanaon who are Ulama and professionals in the enactment of expanded Islamic code of the Muslim Personal Law in the Bangsamoro Autonomous Region in Muslim Mindanao. The study was done through survey method by distributing questionnaire to 300 respondents. To determine the number of participants, purposive sampling technique was used in collecting the samples, and random sampling in selecting the number of respondents involved in the study. The major findings of the study showed that most of the respondents claimed that because of the absence of some of the Islamic laws in PD1083, it is hard for them to incorporate the true teachings of Islam in their field of work and expertise in relations to some of the issues and facts in PD 1083 which are un-Islamic. Being religious leaders, they have heavy burden of guilt as they think of the sin it is coupled in some of the provisions in the Code which have to be amended. In fact, the secular law is still the main basis and the law being used which is opposite to the penal law. Also, an emphasis on the need to incorporate in the enactment of expanded Islamic Code of the Muslim Personal Law in the BARMM the possible Islamic laws such as in the aspects of Islamic Criminal law, Islamic Judicial System and Islamic Finance. Findings further denote on the considerations of all the possible problems that will be encountered in the enactment of expanded Islamic Code of the Muslim Personal Law in the BARMM. Thus, it is hereby recommended that in the critical review on Muslim Code in the enactment of the expanded Islamic code of the Muslim Personal Law in the Bangsamoro Autonomous Region in Muslim Mindanao, that the Congress has its own role, say and participation as to the approval on the total enactment of the said expanded Islamic Code, and there approval should be in the affirmative side. Also, an emphasis that the enactment is applicable only to Muslims without prejudice to Non-Muslims, and this has to reach the National Level assuring all the Islamic laws to be incorporated. Also, it is recommended to integrate Islamic Criminal Law on Hudud and Qisas like death penalty for those crimes fall on this punishment, the same with the cutting of hands to those proven thieves beyond reasonable doubt, and not only Ta’zir punishment. Also, it is recommended for the need of Judicial System in the BARMM and in the High Court and District Court. Additional recommendation is for the Supreme Court to have representatives who are truly knowledgeable in the Qur’an and Sunnah of the Prophet Muhammad (S.A.W.), and in English or Secular law, those who are both cognizant in the areas of learning and teaching in both fields. Moreover, an emphasis on the establishment of Islamic Windows, Islamic Banking, Islamic Insurance, Islamic Cooperatives, Islamic Pawnshop and others in the recommendation of the incorporation of Islamic Finance in expanded Code. Finally, a rationale on the passage of the recognized revision is far recommended, and the full support of its people in its realization.